Positive steady states of the S–K–T competition model with spatially heterogeneous interactions. (December 2020) - Wang, Yu-Xia
Abstract: This paper is concerned about the S–K–T competition model with spatially heterogeneous interactions, in which the two competing species are identical in all aspects except for their interspecific competitions. Under small variations of interspecific competitions, a good understanding of the dynamics and the structure of the set of steady states is gained by the Lyapunov–Schmidt procedure and detailed analysis. The results reveal that the role that the spatial heterogeneity plays in the coexistence of the competing species can be rather interesting and complicated. Either stable or unstable coexistence state can be produced by suitable spatial heterogeneity, so the spatial heterogeneity can be either favorable or unfavorable for the coexistence of competing species.